Histiocytic Sarcoma of Tibia: A Rare Case Report and Review of Literature - Kendre, Ajita; Zade, Bhooshan; Chandra, Prasant (South Asian Journal of Cancer, 2022)
Histiocytic sarcoma is a rare disorder and there has been a lot of confusion and debate regarding its diagnosis and treatment. The World Health Organization (WHO) in 2008 aided in the standardization of diagnosis of histiocytic sarcoma; however, the treatment protocols are still not clear and the treatment is on the line of other hematological malignancies.This study intends to report a rare case of histiocytic sarcoma and the treatment protocol used and analysis of available literature. The usual sites of histiocytic sarcoma are the lymphoreticular system, skin, and gastrointestinal tract, but solitary bone involvement is rare.This disease being a localized one was treated locally with surgical curettage followed by radical radiation therapy. Systemic therapy was not offered to this patient and has been reserved in case a patient gets a systemic recurrence as done in most cases of B cell lymphoma.Based on follow-up until now, the patient is disease-free and doing well. Thus, this treatment protocol appears apt for this concerned patient; however, there is a need for a large-scale analysis of various reported cases to establish a standardized treatment protocol for this rare and aggressive disease.
Keywords: Hematopoietic malignancy of tibia; Histiocytic sarcoma; Neoplasm of histiocytic origin; Primary histiocytic sarcoma of bone; Rare Neoplasm of bone; Reticulo sarcoma